Silicon application enhances drought resilience in buckwheat: a comparative study of three varieties - Krucky, Jiri; Hejnak, Vaclav; Vachova, Pavla; Gupta, Aayushi; Kubes, Jan; Popov, Marek; Skalicky, Milan (Frontiers in Plant Science, 2025)
This study evaluated the effects of foliar silicon (Si) application on physiological and biochemical traits in three buckwheat lines (La Harpe, Panda, Smuga) grown under optimal (control) and drought stress conditions. Plants were cultivated under controlled conditions with four treatments: Control (80% water availability), Drought (40%), Control + Si, and Drought + Si (0.5 mM Na2SiO3·9H2O applied to foliage). Water stress significantly reduced relative leaf water content (RWC), osmotic potential (Ψs), photosynthetic pigments, and gas exchange parameters (A, E, gs) in all varieties. It also increased malondialdehyde (MDA), total flavonoid content (TFC), total antioxidant capacity (TAC), and 5-methylcytosine (5mC), while Fv/Fm remained unchanged, indicating sustained photosystem II activity. However, varietal differences were evident. La Harpe and Panda showed lower RWC, Ψs, A, E, and gs under drought than Smuga. La Harpe had the highest MDA accumulation in roots, increased 5mC levels in leaves, and was the only line with decreased water use efficiency (WUE). Smuga exhibited the highest natural proline level and the strongest proline increase under drought. Foliar Si application reduced MDA and enhanced antioxidant activity (TFC, TAC) in both roots and leaves across all varieties, under both water regimes. The strongest antioxidant response was observed in La Harpe. Si also improved photosynthetic pigment levels, likely contributing to the protection of the photosynthetic apparatus under drought stress. Its effects on RWC, Ψs, and gas exchange under drought were variety-specific: La Harpe and Panda responded positively, while Smuga showed minimal changes. Group correlation analysis under drought showed that Smuga had the strongest positive correlations between plant health traits and stress responses, suggesting effective physiological coordination. Panda showed moderate, and La Harpe negative, correlations. After Si application, these relationships improved most in Smuga, moderately in Panda, and least in La Harpe. Overall, the results reveal clear genotype-specific responses to foliar-applied Si in buckwheat. Silicon improved antioxidant defenses, mitigated drought-induced oxidative stress, and supported physiological functions, particularly in Smuga. These findings support using Si as a promising tool to enhance drought resilience in buckwheat cultivation.